2008
DOI: 10.1139/t07-095
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the annual thermal response of an earth dam for the assessment of the hydraulic conductivity of its compacted till core

Abstract: Heat carried by the seepage water along hydraulic flow lines can serve as a natural tracer to help detect contrasting hydraulic conductivities in embankment dams. Thermal monitoring was realized on the 94.5 m high QA-01 embankment dam in northern Quebec to characterize the temperature distribution across its entire section. The analysis of the annual thermal response of the dam clearly showed a zone of higher seepage velocities in the compacted till core. Approximations concerning the increased hydraulic condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…4) subtracted from the data of Smith and Konrad. 23 By attempting some simulations, it was recognized that in the short-time simulation (1 month), the effects of air and water temperature on temperature distribution inside the dam was restricted at a distance of 5 m from the dam surface (presented later), meaning that air and water temperature boundary conditions did not affect the results of the computed area. A constant heat injection rate of 820 W/m or 15 W/m was correspondingly assigned along the entire length of the standpipe or electrical wire in a 2-day period (Fig.…”
Section: Boundary Conditionmentioning
confidence: 99%
“…4) subtracted from the data of Smith and Konrad. 23 By attempting some simulations, it was recognized that in the short-time simulation (1 month), the effects of air and water temperature on temperature distribution inside the dam was restricted at a distance of 5 m from the dam surface (presented later), meaning that air and water temperature boundary conditions did not affect the results of the computed area. A constant heat injection rate of 820 W/m or 15 W/m was correspondingly assigned along the entire length of the standpipe or electrical wire in a 2-day period (Fig.…”
Section: Boundary Conditionmentioning
confidence: 99%
“…Heat carried by the seepage water along a hydraulic flow line can therefore serve as a natural tracer to help detect zones with contrasting hydraulic conductivities. More details on passive thermometry are included in Smith & Konrad (2008).…”
Section: Specific Thermal Monitoringmentioning
confidence: 99%
“…Numerical simulations have been employed in various studies to interpret the measured temperature variations within dams (e.g., Smith and Konrad 2008;Opali ński et al 2016;Song and Yosef 2017). Smith and Konrad (2008) used seasonal variations in reservoir temperature measured by point sensors along the submerged upstream face of a dam, and within the embankment dam itself, to identify a layer exhibiting elevated leakage within the compacted till core. Simulations using a 2D finite element model with coupling between heat transport and water flow indicated that the layer's hydraulic conductivity was approximately 20 times greater than that of the surrounding core.…”
Section: Introductionmentioning
confidence: 99%